Clinical and laboratory features and treatment approaches of pregnant woman with acute appendicitis - Karaali, Cem; Egemen Ertas, Ibrahim; Sert, Ismail; Burak Oztop, Mehmet; Ustun, Mehmet; Aydin, Cengiz; Emiroglu, Mustafa (Annals of Medical Research, 2021)
Aim: Since it is difficult to diagnose acute appendicitis (AA) in pregnant women, the negative appendectomy and complicated appendectomy rates are higher than the normal population. However, both negative appendectomies and complicated appendicitis have negative effects on the fetus and mother. This study aims to evaluate the patients who underwent appendectomy during pregnancy according to clinical, laboratory and imaging findings. In addition, the Neutrophil-Lymphocyte ratio (NLR) and Platelet-Lymphocyte ratio (PLR) parameters, which are used in the evaluation of pregnant AA patients in the literature, will be evaluated. Material and Methods: Between January 2013 and January 2020, pregnant patients operated for AA were retrospectively analyzed. The patients were evaluated in terms of age, gestational age, clinical, laboratory and imaging findings, operation information, length of hospitalization, pathology results and complications.Results: Twelve patients were included in the study. The mean age of the patients was 29.3 ± 7.38 (min-max 17-41). Three patients were in the 1st trimester (two intrauterin and one extrauterin tubal pregnancy), seven were in the 2nd trimester, and two were in the 3rd trimester. All patients applied with abdominal pain and no appendix could be visualized in any patient on ultrasound imaging. In our study, the average of WBC (White Blood Cell), PDW (Platellet-Distribution Widht), NLR and PLR values were found to be as 13.2 (mcL), 16.9 (%), 3.4 and 79.2, respectively.Conclusion: In our study, a clear distinctive finding to be used in detecting pregnant appendicitis could not be reached. Although imaging and laboratory findings play a role in assisting the diagnosis of AA, our study has revealed that the most important criterion in the diagnosis of AA in pregnant patients is that the general surgery and gynecology team evaluate the patient together.
Keywords: Appendicitis; pregnancy; neutrophil lymphocyte ratio; platelet lymphocyte ratio